Care from a gender and law perspective in Cuba - Páez, Lissett D.; López Pretel, María Isabel (Filanderas, 2023)
The feminization of care is a social phenomenon that deserves to be focus with a comprehensive approach. The objective of this paper is to analyze care work in Cuba, so that it is understood as a universal right, from the paradigm of co-responsibility and empowerment. For such purposes, theoretical methods such as exegetical-analytical and comparative legal are used, which allow reaching significant results regarding care work in Cuba. The need for its inclusion in public policies and its analysis from a gender and rights perspective is highlighted.
Keywords: Co-responsability; Care; Rights; Empowerment; Gender